Dislexia: estudo correlacional de docentes da língua portuguesa do ensino fundamental público e particular - Daruiz, Silvani (2008)
The present study investigated the dyslexia, dificulty for the learning of reading, of congenital origin, in its neurofunctional aspects, related to the new technology of brain image, undoing mistakes that considered it an emotional reaction, an inadequate behavior, an escape to the pertaining of school responsibilities.It aimed to spread a new level of understanding of this specific malfunction that affects the reading and not, the intellectual capacities, presenting it as an imperfection of the language system, in the level of the speaking module, harming phonemics conscience and, thus, the capacity of segmenting the word, verbalized in its underlying sounds, resulting a difficulty for the apprentice, in discovering and dominating the code of reading.It was intended to evaluate how this new knowledge is applied to take the professor, in its pedagogical practice, to the identification of the pointers of the dyslexia and to assist the carrier of this riot to surpass its difficulties and to insert themselves in the pertaining of school and social community.The research objectified to understand the information levels on the dyslexia, existing in 27 professors of Portuguese Language of 5 to 8 grades of the Middle School this being 17 from the public schools and 10 from particular ones, no matter their graduation, age and time of service. The participants had answered a questionnaire that contained questions on the dyslexia with objective answers. The results had disclosed unfamiliarity on the ethiological-causal aspects of the dyslexia where 29.6% don't consider the genetic, hereditary and neurological aspects as cause of the upheaval and 33.3% as predisponent factor. In the sample, 22.3% relate the causes of the dislexia to low intelligence and 48.1% to the attention lack, 29.6% consider as causal factor of the upheaval the social-economic conditions; 37% problems of lettering and inadequate formation of professor and 74%, emotional problems of the pupil. The study concluded that the level of information of the participant professors was insufficient to identify signals of risk for the dyslexic upheaval.